Reconstruction of late Holocene autumn/winter precipitation variability in SW Romania from a high-resolution speleothem trace element record - Warken, Sophie F.; Schröder-Ritzrau, Andrea; Spötl, Christoph; Frank, Norbert; Arps, Jennifer; Mangini, Augusto (Earth and planetary science letters, 2018)
We present the first high-resolution trace element (Mg/Ca, Sr/Ca, Ba/Ca) record from a stalagmite in southwestern Romania covering the last 3.6 ka, which provides the potential for quantitative climate reconstruction. Precise age control is based on three independent dating methods, in particular for the last 250 yr, where chemical lamina counting is combined with the identification of the 20th century radiocarbon bomb peak and 230Th/U dating. Long-term cave monitoring and model simulations of drip water and speleothem elemental variability indicate that precipitation-related processes are the main drivers of speleothem Mg/Ca ratios. Calibration against instrumental climate data shows a significant anti-correlation of speleothem Mg/Ca ratios with autumn/winter (October to March) precipitation (r = −0.61, p < 0.01), which is statistically robust when considering age uncertainties and auto-correlation. This relationship is used to develop a quantitative reconstruction of autumn/winter precipitation. During the late Holocene, our data suggest a heterogeneous pattern of past regional winter hydroclimate in the Carpathian/Balkan realm, along with intermittent weakening of the dominant influence of North Atlantic forcing. In agreement with other regional paleo-hydrological reconstructions, the observed variability reveals periodically occurring strong NW-SE hydro-climate gradients. We hypothesize, that this pattern is caused by shifts of the eastern edge of the area of influence of the NAO across central-eastern Europe due to the confluence of North Atlantic forcing, and other climatic features such as the East Atlantic/Western Russia (EAWR) pattern.